Implementasi Desain Ruang Kelas Dalam Mengembangkan Sosial Emosional Anak Usia Dini di RA Aisyiah Jintap Ponorogo - Muhammad Azam Muttaqin; Cahya Mutiara Anisa; Elsa Nanda Noviani (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
The purpose of this study was to find out the application of class design in the social-emotional development of early childhood at RA Aisyiah Jintap Ponorogo. This study used qualitative methods with data collection techniques obtained using observation, interviews and documentation techniques. As well as using data validation techniques and data analysis. Based on the research results, class design can provide children with an understanding of social emotions, namely social emotional behavior, social emotional learning in children, and social emotional self-control.